45+6x+22=75+4x

Simple and best practice solution for 45+6x+22=75+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 45+6x+22=75+4x equation:


Simplifying
45 + 6x + 22 = 75 + 4x

Reorder the terms:
45 + 22 + 6x = 75 + 4x

Combine like terms: 45 + 22 = 67
67 + 6x = 75 + 4x

Solving
67 + 6x = 75 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
67 + 6x + -4x = 75 + 4x + -4x

Combine like terms: 6x + -4x = 2x
67 + 2x = 75 + 4x + -4x

Combine like terms: 4x + -4x = 0
67 + 2x = 75 + 0
67 + 2x = 75

Add '-67' to each side of the equation.
67 + -67 + 2x = 75 + -67

Combine like terms: 67 + -67 = 0
0 + 2x = 75 + -67
2x = 75 + -67

Combine like terms: 75 + -67 = 8
2x = 8

Divide each side by '2'.
x = 4

Simplifying
x = 4

See similar equations:

| 4+4(4x+1)=-32+6x | | sen(t)=2(t) | | 8k=6j | | 2/5x-4/9=-6 | | 8x-8/8=-11 | | 14x-(2x-3)=51 | | 5x-2x/3= | | 2y+1=4x-5 | | 0.20=0.8x+0.2y | | 10+2x+40=180 | | sin(t)=2(t) | | c+6(8)=53 | | -63=-54t | | 23+n=12 | | 2x+36=x-4 | | 6c+3.50+5.50=51 | | 5z-7=6z-6 | | 9+1/9= | | 35x^2+47x+6=0 | | 40=80u | | sin(t^3)=2(t^3) | | (4+4i)(-4+4i)= | | -4m+8=20 | | 18=2x-4(-4x+18) | | 1r+t-8r+13t= | | 4(5z+1)-7=157 | | 3+6(1-6x)= | | (6x)3=2+8 | | 4/7x=x/7 | | 2sin(4x-1)=1 | | 66=31-5(x-4) | | y=-1/3x-7 |

Equations solver categories